A5 9 Stellar replacements - Shkullaku, Marin; Matkin, Eleanor; Morriss, Luke (Physics Special Topics, 2023)
In this paper we investigated what the impact that replacing the Sun with other main sequence stars, with the same apparent bolometric magnitude, would have on the incoming radiation at the surface of the Earth. We considered the effects of atmospheric absorption on the black body radiation of the stars. We found that the relationship between star type and incoming radiation peaks at Sun-like stars and then drops off for smaller and larger classifications.